Evaluating the implementation of E-portfolio-based learning in ELT through the CIPP model: A qualitative descriptive study in Indonesia - Ali, Raden Muhammad; Hadi, Samsul; Purbani, Widyastuti; Nuriyah Muso Utomo, Sinta; Kunta Biddinika, Muhammad; Hastuti, Dwi (Universitas Ahmad Dahlan, 2025)
E-portfolios have increasingly been integrated into higher education to promote reflection, documentation, and learner autonomy; however, their effectiveness in English Language Teaching (ELT) in Indonesia remains insufficiently examined. This study evaluates the use of e-portfolio-based learning in an Evaluation in ELT course by employing the Context, Input, Process, and Product (CIPP) evaluation model. Four research questions guided the investigation, focusing on the relevance of the programme context, the adequacy of inputs, the implementation processes, and the resulting learning outcomes. Using a descriptive qualitative design, data were collected through classroom observations, semi-structured interviews, and documentation of students’ e-portfolios. The participants consisted of one lecturer and thirty-seven seventh-semester students (ten males and twenty-seven females) enrolled in the course during the 2022/2023 academic year; additionally, three students were purposively selected for in-depth interviews. The findings indicate that (1) the context supported the adoption of e-portfolios as it aligned with course needs and learning objectives; (2) the input—including digital facilities, infrastructure, and access to online tools—was adequate for implementation; (3) the process showed active student engagement, although challenges such as connectivity issues, device limitations, and time constraints were present; and (4) the product demonstrated positive learning outcomes, including improved documentation practices, better understanding of course material, and increased digital literacy. The study underscores the potential of e-portfolios to enhance ELT learning and suggests the need for more structured feedback mechanisms and technical support to optimise future implementation.